Conservation status of buff-breasted sandpipers (Tryngites subruficollis) in the Western Hemisphere: a conservation genetic approach - Lounsberry, Zachary T. (Kansas State University, 2012)
Range-wide estimates of shorebird (Aves: Charadriiformes) populations suggest sharp declines in population sizes across a range of species. Efforts to accurately assess the conservation status of wild populations are becoming increasingly vital to species management. One shorebird of conservation concern, the Buff-breasted Sandpiper (Tryngites subruficollis), is a New World migrant which winters in southeastern South America and breeds in the arctic. To establish an updated conservation status for Buff-breasted Sandpipers, we conducted a molecular survey of wild populations on spatial and temporal scales. We analyzed patterns of global population structure, demographic trends, and phylogeography using nine polymorphic microsatellites and two mitochondrial DNA (mtDNA) markers, cytochrome b and the control region, among 477 individuals across their distributional range. To empirically assess the impact of population declines on genetic diversity, we also surveyed segments of the same two mtDNA markers from 220 museum specimens collected across a 135-year period. Contemporary microsatellite and mtDNA analyses revealed that Buff-breasted Sandpipers are admixed on a global scale, with effective population size estimates ranging from 2,657 to 16,400 birds and no signal of a recent genetic bottleneck. Contemporary mtDNA analyses suggested a pattern of haplotype diversity consistent with a historic radiation from a single refugium which we estimated to have occurred between 8,000−45,000 years before present. Using five measures of mtDNA diversity (haplotype and nucleotide diversity, trend analyses of haplotype richness, Watterson’s estimate of theta, and phi-statistics), as well as a Bayesian Skyline reconstruction of demographic trends in effective population size (N[subscript]e[subscript]f), we concluded that substantial mtDNA diversity and N[subscript]e[subscript]f had not been lost as a result of the population declines in this species. While genetic diversity did not appear to have been lost due to population losses, management efforts must focus on preventing future losses in order for wild populations to remain viable. Our results suggested that the global population of Buff-breasted Sandpipers should be treated as a single, panmictic conservation unit and that successful management must focus on preventing further declines and habitat fragmentation.
Keywords: Buff-breasted Sandpiper; Tryngites subruficollis; Conservation genetics; Phylogeography; Microsatellite; mtDNA; Ecology (0329)